THE NUCLEAR FAMILY IN MODERN TERRORISM (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The article aims to present the relationship between the nuclear family and its involvement in modern forms of terrorism. It reveals the reasons for the emergence of family terrorism based on the inculcated belief that certain moral qualities play a major role in the upbringing within the nuclear family. It also presents the challenges which affect parenting at the nuclear family level that must find their solution before many families become victims to a particular type of terrorism, be it political, religious, ethnic, or racial. In the dynamics of the studied problem, the achievements of scientific theory and the derivation of good practices face growing demands, the need to balance the used resources, satisfy the norms of international and national law, and at the same time the growing competitiveness of terrorist organizations and networks. This gives reason and gives rise to the need for continuous scientific research despite the indisputable achievements in the field, as well as the respectable publications of several leading authors. In the interest of the research, the methods of analysis and synthesis, and temporal monitoring of open sources, including scientific publications and information media, with a wide territorial scope, were used. To further enrich the analysis, in-depth interviews were conducted with experts in the field of countering radicalization and terrorism from Bulgaria, Israel, and Great Britain. Individual cases were also analyzed using the "case study" method, or the so-called "case studies".